2020
DOI: 10.2147/cmar.s256347
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tanshinone IIA Suppresses Glioma Cell Proliferation, Migration and Invasion Both in vitro and in vivo Partially Through miR-16-5p/Talin-1 (TLN1) Axis</p>

Abstract: Background: Tanshinone IIA (TIIA) is one of the active constituents derived from the rhizome of Danshen, a traditional Chinese herbal. Recently, microRNAs (miRNAs) have been suggested to be associated with the anticancer role of TIIA. However, it remains vague of the interaction between miRNAs and TIIA in glioma, a common aggressive brain tumor in humans. Methods: Expression of miRNA (miR)-16-5p and talin-1 (TLN1) was detected using reverse transcription-quantitative polymerase chain reaction and Western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Frontiers in Genetics frontiersin.org You et al, 2020;Liu et al, 2021). Furthermore, they also have anti-diabetes, anti-inflammation, antioxidant and anticancer therapeutic effects (Wang L. et al, 2017;Maione et al, 2018;Jia et al, 2019;Li et al, 2021;Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org You et al, 2020;Liu et al, 2021). Furthermore, they also have anti-diabetes, anti-inflammation, antioxidant and anticancer therapeutic effects (Wang L. et al, 2017;Maione et al, 2018;Jia et al, 2019;Li et al, 2021;Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In China, herbal medicine combined with radiotherapy and/or chemotherapy has achieved good results in improving the adverse reactions and the quality of life of glioma patients, preventing postoperative recurrence, and prolonging their survival [ 32 – 35 ]. Moreover, several preclinical studies have demonstrated an inhibitory effect of natural compounds extracted from herbal medicines on glioma cell growth [ 36 – 38 ]. In the present study, we focused on curcumol, a well-known herbal medicine and health food supplement in China.…”
Section: Discussionmentioning
confidence: 99%
“…In China, herbal medicine combined with radiotherapy and/or chemotherapy has achieved good results in improving the adverse reactions and the quality of life of glioma patients, preventing postoperative recurrence, and prolonging survival [34][35][36][37]. Moreover, several preclinical studies have demonstrated an inhibitory effect of natural compounds extracted from herbal medicines on glioma cell growth [38][39][40]. In the present study, we focused on curcumol, a well-known herbal medicine and healthfood supplement in China.…”
Section: Discussionmentioning
confidence: 99%